The value of Serum Cholesterol and Triglyceride Levels as Prognostic Markers in the evolution of Respiratory Distress Syndrome in Premature Neonates - عثمان, زينب; عدنان ديوب,; سعاد صقور, (Latakia University Journal -Medical Sciences Series, 2023)
Background: Essential lipids malnutrition can affect maternal health and lead in preterm birth to higher incidence of neonatal respiratory distress syndrome Objectives: The aim of this study was to evaluate early lipid profile in preterm infants and its relationship as prognostic markers with respiratory distress syndrome. Methods: This is an Observational Cohort study included preterm infants with 25 to 34 weeks’ gestation age admitted to the Neonate Unit at Tishreen University Hospital during the study period from March 2021 to March 2022. Blood samples were taken immediately after birth and total cholesterol and Triglyceride levels were measured. Study sample was divided into two groups: Preterm infants who developed RDS and Preterm infants who didn’t develop RDS Results: A statistical study was conducted for 80 preterm infants, 45% of them developed RDS. Analysis of gender among the two groups showed no significant differences between the groups (p=0,3) but there were significant differences regarding to the gestational age and birth weight (p=0,0001 and p=0,001). Mean serum triglyceride and cholesterol were lower in preterm with RDS compared to Non RDS which was statistically significant (p=0,0001). Premature Neonate with early serum cholesterol ≤58.5 and Triglycerid ≤ 43.5 are at risk of developing RDS Conclusion: Preterm newborns with lower Serum Cholestrol and Triglyceride at birth may develop RDS